Homeopathy for allergic rhinitis: A systematic review. - Banerjee, K; Mathie, RT; Costelloe, C; Howick, J (Mary Ann Liebert Inc, 2017)
Objective The aim of this study was to evaluate the efficacy and effectiveness of homeopathic intervention in the treatment of seasonal or perennial allergic rhinitis (AR). Method Randomized controlled trials evaluating all forms of homeopathic treatment for AR were included in a systematic review (SR) of studies published up to and including December 2015. Two authors independently screened potential studies, extracted data, and assessed risk of bias. Primary outcomes included symptom improvement and total quality-of-life score. Treatment effect size was quantified as mean difference (continuous data), or by risk ratio (RR) and odds ratio (dichotomous data), with 95% confidence intervals (CI). Metaanalysis was performed after assessing heterogeneity and risk of bias. Results Eleven studies were eligible for SR. All trials were placebo-controlled except one. Six trials used the treatment approach known as isopathy, but they were unsuitable for meta-analysis due to problems of heterogeneity and data extraction. The overall standard of methods and reporting was poor: 8/11 trials were assessed as ‘‘high risk of bias’’; only one trial, on isopathy for seasonal AR, possessed reliable evidence. Three trials of variable quality (all using Galphimia glauca for seasonal AR) were included in the meta-analysis: nasal symptom relief at 2 and 4 weeks (RR = 1.48 [95% CI 1.24–1.77] and 1.27 [95% CI 1.10–1.46], respectively) favored homeopathy compared with placebo; ocular symptom relief at 2 and 4 weeks also favored homeopathy (RR = 1.55 [95% CI 1.33–1.80] and 1.37 [95% CI 1.21–1.56], respectively). The single trial with reliable evidence had a small positive treatment effect without statistical significance. A homeopathic and a conventional nasal spray produced equivalent improvements in nasal and ocular symptoms. Conclusions The low or uncertain overall quality of the evidence warrants caution in drawing firm conclusions about intervention effects. Use of either Galphimia glauca or a homeopathic nasal spray may have small beneficial effects on the nasal and ocular symptoms of AR. The efficacy of isopathic treatment of AR is unclear.